Subjective Wellbeing and Levels of Clinical Symptomatology in a Transwomen Sample and Men Who Have Sex with Men in Chile - Barrientos-Delgado, J (Routledge, 2016)
This article examines the levels of subjective wellbeing (psychological and social wellbeing, subjective happiness, and satisfaction with life) and clinical symptomatology (anxiety, depression, somatization, hostility, and phobic anxiety) in a transwomen sample (n = 112). The sample was recruited through a snowball procedure in Chile (Santiago, Valparaíso, and Arica). Data obtained are compared to those from a group of men who have sex with men (MSM; n = 323). Results reveal statistically significant differences in the levels of happiness (t(157) = 2.16; p = .03; d = .25), satisfaction with life (t(154) = 3.90; p < .001; d = .47), and purpose in life (scale of psychological wellbeing; t(151) = 1.99; p.04; d = .24) reported by the two groups. The transwomen group shows the lowest scores in all dimensions. However, trans women report higher levels of social coherence (t(432) = −4.96; p < .001; d = .53) on the social wellbeing scale, compared to the MSM group. Regarding their levels of clinical symptomatology, trans women report higher levels of anxiety (t(163) = −6.67; p < .001; d = .78), depression (t(167) = −5.61; p < .001; d = .65), somatization (t(161) = −5.10; p < .001; d = .60), hostility (t(153) = −5.38; p < .001; d = .62), and phobic anxiety (t(164) = −6.70; p < .001; d = .80). Results are discussed on the basis of the context of each group. © 2016 Taylor & Francis.